Design, formulation and evaluation of caffeine chewing gum - Abolfazl Aslani; Fatemeh Jalilian (Advanced Biomedical Research, 2013)
Background: Caffeine which exists in drinks such as coffee as well as in drug dosage forms in the global market is among the materials that increase alertness and decrease fatigue. Compared to other forms of caffeine, caffeine gum can create faster and more prominent effects. In this study, the main goal is to design a new formulation of caffeine gum with desirable taste and assess its physicochemical properties. Materials and Methods: Caffeine gum was prepared by softening of gum bases and then mixing with other formulation ingredients. To decrease the bitterness of caffeine, sugar, aspartame, liquid glucose, sorbitol, manitol, xylitol, and various flavors were used. Caffeine release from gum base was investigated by mechanical chewing set. Content uniformity test was also performed on the gums. The gums were evaluated in terms of organoleptic properties by the Latin-Square design at different stages. Results: After making 22 formulations of caffeine gums, F 11 from 20 mg caffeine gums and F 22 from 50 mg caffeine gums were chosen as the best formulation in organoleptic properties. Both types of gum released about 90% of their own drug content after 30 min. Drug content of 20 and 50 mg caffeine gum was about 18.2-21.3 mg and 45.7-53.6 mg respectively. Conclusion: In this study, 20 and 50 mg caffeine gums with suitable and desirable properties (i.e., good taste and satisfactory release) were formulated. The best flavor for caffeine gum was cinnamon. Both kinds of 20 and 50 mg gums succeeded in content uniformity test.